The External Oblique Intercostal Block: Anatomic Evaluation and Case Series. Issue 11 (9th October 2021) - Elsharkawy, Hesham; Kolli, Sree; Soliman, Loran Mounir; Seif, John; Drake, Richard L; Mariano, Edward R; El-Boghdadly, Kariem
Abstract: Study Objective: We report a modified block technique aimed at obtaining upper midline and lateral abdominal wall analgesia: the external oblique intercostal (EOI) block. Design: A cadaveric study and retrospective cohort study assessing the potential analgesic effect of the EOI block. Setting: Cadaver lab and operating room. Patients: Two unembalmed cadavers and 22 patients. Interventions: Bilateral ultrasound-guided EOI blocks on cadavers with 29 mL of bupivacaine 0.25% with 1 mL of India ink; single-injection or continuous EOI blocks in patients. Measurements: Dye spread in cadavers and loss of cutaneous sensation in patients. Main Results: In the cadaveric specimens, we identified consistent staining of both lateral and anterior branches of intercostal nerves from T7 to T10. We also found consistent dermatomal sensory blockade of T6–T10 at the anterior axillary line and T6–T9 at the midline in patients receiving the EOI block. Conclusions: We demonstrate the potential mechanism of this technique with a cadaveric study that shows consistent staining of both lateral and anterior branches of intercostal nerves T7–T10. Patients who received this block exhibited consistent dermatomal sensory blockade of T6–T10 at the anterior axillary line and T6–T9 at the midline. This block can be used in multiple clinical settings for upper abdominal wall analgesia.